The Microwave Rotational Electric Resonance (RER) Spectrum of Benzothiazole - Hamza El Hadki; Kenneth J. Koziol; Oum Keltoum Kabbaj; Najia Komiha; Isabelle Kleiner; Ha Vinh Lam Nguyen (Molecules, 2023)
The microwave spectra of benzothiazole were measured in the frequency range 2–26.5 GHz using a pulsed molecular jet Fourier transform microwave spectrometer. Hyperfine splittings arising from the quadrupole coupling of the 14N nucleus were fully resolved and analyzed simultaneously with the rotational frequencies. In total, 194 and 92 hyperfine components of the main species and the 34S isotopologue, respectively, were measured and fitted to measurement accuracy using a semi-rigid rotor model supplemented by a Hamiltonian accounting for the 14N nuclear quadrupole coupling effect. Highly accurate rotational constants, centrifugal distortion constants, and 14N nuclear quadrupole coupling constants were deduced. A large number of method and basis set combinations were used to optimize the molecular geometry of benzothiazole, and the calculated rotational constants were compared with the experimentally determined constants in the course of a benchmarking effort. The similar value of the χcc quadrupole coupling constant when compared to other thiazole derivatives indicates only very small changes of the electronic environment at the nitrogen nucleus in these compounds. The small negative inertial defect of −0.056 uÅ2 hints that low-frequency out-of-plane vibrations are present in benzothiazole, similar to the observation for some other planar aromatic molecules.